To Help or Not to Help? Prosocial Behavior, Its Association With Well-Being, and Predictors of Prosocial Behavior During the Coronavirus Disease Pandemic - Haller, Elisa; Lubenko, Jelena; Presti, Giovambattista; Squatrito, Valeria; Constantinou, Marios; Nicolaou, Christiana; Papacostas, Savvas; Aydın, Gökçen; Chong, Yuen Yu; Chien, Wai Tong; Cheng, Ho Yu; Ruiz, Francisco J.; et al. (Frontiers in Psychology, 2022)
The COVID-19 pandemic fundamentally disrupted humans’ social life and behavior. Public health measures may have inadvertently impacted how people care for each other. This study investigated prosocial behavior, its association well-being, and predictors of prosocial behavior during the first COVID-19 pandemic lockdown and sought to understand whether region-specific differences exist. Participants (N = 9496) from eight regions clustering multiple countries around the world responded to a cross-sectional online-survey investigating the psychological consequences of the first upsurge of lockdowns in spring 2020. Prosocial behavior was reported to occur frequently. Multiple regression analyses showed that prosocial behavior was associated with better well-being consistently across regions. With regard to predictors of prosocial behavior, high levels of perceived social support were most strongly associated with prosocial behavior, followed by high levels of perceived stress, positive affect and psychological flexibility. Sociodemographic and psychosocial predictors of prosocial behavior were similar across regions.